Metronomic Oral Topotecan with Pazopanib Is an Active Antiangiogenic Regimen in Mouse Models of Aggressive Pediatric Solid Tumor - Kumar, Sushil (2011)
Purpose: Low dose metronomic (LDM) chemotherapy, combined with VEGF signaling pathway inhibitors, is a highly effective strategy to coordinately inhibit angiogenesis and tumor growth in many adult preclinical cancer models. We have tested the efficacies of daily oral LDM topotecan alone and in combination with pazopanib, a VEGF receptor inhibitor, in three pediatric extracranial solid tumor mouse models.Experimental Design: in vitro dose-response study of topotecan and pazopanib was conducted on several neuroblastoma, osteosarcoma, and rhabdomyosarcoma cell lines. in vivo antitumor efficacies of the LDM topotecan and pazopanib as single agents and in combination were tested on 4 subcutaneous xenograft models and on 2 neuroblastoma metastatic models. Circulating angiogenic factors such as circulating endothelial cells (CEC), circulating endothelial progenitor cells (CEP), and microvessel densities were used as surrogate biomarker markers of antiangiogenic activity.Results: in vitro, topotecan caused a dose-dependent decrease in viabilities of all cell lines, while pazopanib did not. in vivo, combination of topotecan + pazopanib (TP + PZ) showed significant antitumor activity and significant enhancement in survival compared with the respective single agents in all models. Reductions in viable CEP and/or CEC levels and tumor microvessel density were correlated with tumor response and therefore confirmed the antiangiogenic activity of the regimens. Pharmacokinetic studies of both drugs did not reveal any drug-drug interaction.Conclusion: Metronomic administration of TP + PZ showed a statistically significant antitumor activity compared with respective single agents in pediatric tumor mouse models and represent a valid option as a maintenance therapy in aggressive pediatric solid tumors. Clin Cancer Res; 17(17); 5656-67. (C)2011 AACR.